Norrland’s Regional Literature as World Literature: Per Olov Enquist’s Literary Work - Herrmann, Elisabeth (Journal of Northern Studies, 2014)
The work of Per Olov Enquist, one of the most important contemporary Swedish authors, is known far beyond Sweden’s and Europe’s borders, and thus even received in North America. A great many of his fictional documentary works and dramatic plays, the biographies of poets such Hans Christian Andersen, Selma Lagerlöf, Knut Hamsun, and August Strindberg, as well as the bestselling novels Lewis Journey, The Royal Physician’s Visit and The Book about Blanche and Marie, have secured a firm position for this Norrland author in the canon of world literature. The continuous transgression of the borders between historical facts and their fictionalization builds the basic characteristic of Enquist’s literature. For Enquist, the goal of writing is to sound out the “innermost space of human existence.” He is eager to explore those secrets and ambiguities that underlie certain historical events or individual life stories. How is individual life determined? And how do individuals find their place in the world? In several of his works, the author uses the metaphor of drawing topographical maps to illustrate the search for one’s own identity as an attempt to position oneself in the world. Starting from his memory of lying on the kitchen floor as a young boy and drawing maps of his native village Hjoggböle, the area around Bureå, the Västerbotten and Norrland region as well as of his native country Sweden, Enquist reveals to his readers what it is that he considers literature to be: the compression of real signs into a fictional space which resembles reality, but, at the same time, moves beyond the boundaries of reality. Through an analytical synopsis of those works that use the motif of map-drawing as a central theme and often refer to each other in direct intertextual reference, namely the novel Captain Nemo’s Library, the essay collection Kartritarna [‘The cartographers’], and Enquist’s biography Ett annat liv [‘A different life’], this article examines the metaphorical function and poetological meaning that the depiction of the author’s own region and home as well as references to his own life story and origin have in Enquist’s work.